The Media Framing of a Toxic Celebrity. How the Slovak Press Portrayed the Businessman Accused of Journalist’s Murder - Rončáková, Terézia; Virostková, Lucia; Polievková, Petra; Kravčák, Peter (Communication Today, 2024)
The term “celebrity” is neutral and designates people with both admirable and intimidating histories. The media tend to overlook the moral dimension of celebrities and frame them by their own rules. This study describes the media framing of a toxic celebrity in Slovakia: the controversial businessman Marián Kočner, currently on trial for ordering the murder of investigative journalist Ján Kuciak in 2018. Long before the killing, Kočner had become well-known to the broader public and appeared as exerting influence on political events. The authors have analysed media texts related to Kočner from 1998 to 2017 and identified 12 generalising frames which could be applied to frame any toxic celebrity. These frames have been aptly titled (Chichikov, mafioso, key player, toxic person, tycoon, Black Peter, Richman, spin doctor, Robin Hood, narcissist, showman, innovator), defined and related to the tonality of the texts (positive, negative, neutral) and to the timeline of Kočner’s media image. The study refers to the only gradually increasing negativity of his media framing along with the overall weak sensitivity of the media to his moral character and highlights the difference between serious and tabloid media, with the framing in the latter focused on luxury and gossip reporting.